Growth and Production of Rice (Oryza sativa L.) on a Variety of Combination Dosage Liquid Organic Fertilizer and Inorganic - Herman Herman (Lembaga Sembilan Tiga Community, 2020)
This study aims to determine the effect of various doses of the combination of the use of liquid organic fertilizer (bio-urine) and inorganic fertilizer on rice plants. The study was conducted in Sabantang Hamlet, Toddopulia Village, Kec. Tanralili Kab. Maros from January to May 2017. This research was conducted in an experimental form using the Randomized Block Design (RBD) method, which was divided into three groups, each group was divided into 6 treatments consisting of control / farmer method (100 kg NPK + 125 kg urea / ha), Without POC Bio-Urine + 300 kg / ha NPK +125 kg / ha Urea), 3 liters / ha POC Bio-Urine + 250 kg / ha NPK + 125 kg / ha Urea, 6 liters / ha POC Bio- Urine + 200 kg / ha NPK + 125 kg / ha Urea, 9 liters / ha POC Bio-Urine + 150 kg / ha NPK + 125 kg / ha Urea, and 12 liters / ha POC Bio-Urine + 100 kg / ha NPK + 125 kg / ha Urea. So that there are 18 observation units. Based on the results of the research that has been carried out, it can be concluded that the combination of using liquid organic fertilizer (Bio-urine) and inorganic fertilizers with a dose of 6 liters of POC Bio Urine + 200 kg NPK + 125 kg Urea / ha. Giving the best influence on growth and productivity in rice plants.